Antibacterial Activity Test of Ethanol Extract and Fraction of Carrot Leaf (Daucus Carota L.) Against Staphylococcus Aureus - Akune, Nadia Ayuwanda S; Rahmawati, Ismi; Sulaiman, Saifullah (Jurnal Multidisiplin Madani, 2024)
Staphylococcus aureus is one of the bacteria that cause acne and can cause skin and organ damage because bacteria can defeat the body's defences. Carrot leaf extract has antibacterial power or inhibitory activity against S. aureus. This study aims to determine the inhibition value and antibacterial activity of ethanol extract and n-hexane fraction of carrot leaves. The research method consists of extraction using 96% ethanol and fractionation using water, ethyl acetate, and n-hexane. The antibacterial activity of carrot leaf extracts and fractions was carried out using the pitting method as well as the use of gentamicin positive control and DMSO negative control. The results showed that 96% ethanol extract of carrot leaves with a concentration of 30% had inhibition against S. aureus bacteria with a value of 7.8 mm or weak inhibitory activity, and the ethyl acetate fraction of carrot leaves with a concentration of 20% had inhibition against S. aureus bacteria with a value of 11.27 mm or strong inhibitory activity. Therefore, ethyl acetate fraction of carrot leaves have inhibition against S. aureus bacteria with strong inhibitory activity compared to other test solutions and is equivalent to gentamicin positive control